(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The scientific heritage of Ulugbek began to be studied in the 15th century. For example, one of the historians of that time, Abdurazzak Samarkandi, in part of his work entitled "Matla’i Sa’dayn va Majmai Bahrain" under the title "Mention on the buildings built in Dorussaltan Samarkand" wrote about Ulugbek: "The country of Movaraunnahr has reached the peak of governance and prosperity , and the young prince Mugisuddin Mirza Ulugbek began to build tall buildings in beautiful places. showed a desire,” said ezgan. In his work, the author says that Ulugbek built a madrasah and a house facing each other on the square in the city center (in the source he is named E.B. in the city center). He gives information that he spent several years building these houses of knowledge. They were a “house” built with an extremely high dome on the site of the Ulugbek madrasah (built in 1417-1420) and the Sher-Dor madrasah, which has survived to this day as a good architectural structure.